The 2011 M = 9.0 Tohoku oki earthquake more than doubled the probability of large shocks beneath Tokyo. Issue 11 (6th June 2013) - Toda, Shinji; Stein, Ross S.
Abstract [1] The Kanto seismic corridor surrounding Tokyo has hosted four to five M ≥ 7 earthquakes in the past 400 years. Immediately after the Tohoku earthquake, the seismicity rate in the corridor jumped 10‐fold, while the rate of normal focal mechanisms dropped in half. The seismicity rate decayed for 6–12 months, after which it steadied at three times the pre‐Tohoku rate. The seismicity rate jump and decay to a new rate, as well as the focal mechanism change, can be explained by the static stress imparted by the Tohoku rupture and postseismic creep to Kanto faults. We therefore fit the seismicity observations to a rate/state Coulomb model, which we use to forecast the time‐dependent probability of large earthquakes in the Kanto seismic corridor. We estimate a 17% probability of a M ≥ 7.0 shock over the 5 year prospective period 11 March 2013 to 10 March 2018, two‐and‐a‐half times the probability had the Tohoku earthquake not struck.